Tumor-Infiltrating Lymphocytes (TILs) and Risk of a Second Breast Event After a Ductal Carcinoma in situ - Farolfi, Alberto; Petracci, Elisabetta; Serra, Luigi; Ravaioli, Alessandra; Bravaccini, Sara; Ravaioli, Sara; Tumedei, Maria Maddalena; Ulivi, Paola; Canale, Matteo; Puccetti, Maurizio; Falcini, Fabio; Folli, Secondo; et al. (Frontiers in Oncology, 2020)
Women with a diagnosis of ductal carcinoma in situ (DCIS) have a high risk of developing a second breast event (SBE). The immune system might play a role in trying to prevent a SBE. Patients diagnosed with DCIS were identified in the population-based cancer registry of Area Vasta Romagna from 1997 to 2010. Median follow-up is 8.5 years. Tumor-infiltrating lymphocytes (TILs) were evaluated both in index DCIS and in SBE. The main endpoint was to assess the association between TILs' levels in index DCIS and risk of a SBE. Out of 496 DCIS patients, 100 SBEs (20.2%) were identified: 55 ipsilateral (11.1%) and 43 contralateral (8.7%). The distribution of TILs was heterogeneous, but significantly associated with grade, necrosis, screen detection and type of surgery. Patients stratified according to TILs percentage (≤ 5% and > 5%) did not show a statistically significant difference in the 5-year cumulative incidence of SBEs: 14.9% (95% CI 11.3-19.1) and 11.0% (95% CI, 6.9-16.2), respectively (p = 0.147). In the subgroup of patients who did not receive radiotherapy, TILs >5% were associated with a reduced risk of SBE (HR 0.34, 95% CI 0.14-0.82, p =0.016). Although we did not find any significant association between TILs and SBE, further studies evaluating their role according to radiotherapy are warranted.